Study of the influence of excitation regulation of synchronous machines of pumping stations on the modes of power supply networks of the power system - Obid Y. Nurmatov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: in our republic there are 1698 pumping stations (PS) for irrigation, there are also many PS in other areas; most PS are equipped with electric drives with synchronous motors. The developing structure of the country's energy system requires research to identify the influence of regulation of various modes of such PS on the modes of the power supply networks of the energy system. Aim: to consider the influence of excitation regulation of synchronous machines of PS drives on the modes of the power supply networks in order to develop recommendations that improve the efficiency of their joint operation. Methods: to solving the set problems, the methods of mathematical and simulation modeling, as well as the analysis of calculations of joint modes of PS and the power supply network were used. Results: the influence of excitation control systems of pumping stations on the modes of the power supply networks of the power system is shown, recommendations for improving the modes are given.